Effect of cellulose nanocrystal polymorphs on mechanical, barrier and thermal properties of poly(lactic acid) based bionanocomposites1. Issue 74 (13th August 2015) - Dhar, Prodyut; Tarafder, Debashis; Kumar, Amit; Katiyar, Vimal
<x xml:space="preserve">Abstract</x> Cellulose nanocrystals (CNCs) using different cellulose polymorphs have been fabricated from raw bamboo pulp. Their structural and morphological effects on the mechanical, barrier and thermal properties of poly(lactic acid) have been investigated.